1998
DOI: 10.1038/bjc.1998.79
|View full text |Cite
|
Sign up to set email alerts
|

Dihydropyrimidine dehydrogenase pharmacogenetics in patients with colorectal cancer

Abstract: Summary Individuals with a deficiency in the enzyme dihydropyrimidine dehydrogenase (DPD) may experience severe life-threatening toxicity when treated with 5-fluorouracil (5-FU). As routine measurement of enzyme activity is not practical in many clinical centres, we have investigated the use of DNA mutation analysis to identify cancer patients with low enzyme levels. We have identified two new mutations at codons 534 and 543 in the DPD cDNA of a patient with low enzyme activity and screened the DNA from 75 col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
42
0
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(49 citation statements)
references
References 11 publications
6
42
0
1
Order By: Relevance
“…Exon 14 DPYD mutations showed a statistically significant association with grade 3-4 5-FU toxicity (P ϭ 0.01). The frequency of DPYD in our colorectal cancer population was not significantly different from that reported by Ridge et al 15 (2.7 vs. 4%).…”
Section: Discussionmentioning
confidence: 29%
See 3 more Smart Citations
“…Exon 14 DPYD mutations showed a statistically significant association with grade 3-4 5-FU toxicity (P ϭ 0.01). The frequency of DPYD in our colorectal cancer population was not significantly different from that reported by Ridge et al 15 (2.7 vs. 4%).…”
Section: Discussionmentioning
confidence: 29%
“…10,22 It has subsequently been demonstrated that a number of these individuals were genotypically heterozygous for a mutant DPYD allele, [11][12][13][14][15][16] but data are scant on the frequency of mutations in DPYD among cancer patients. In this study, we showed that the prevalence of the mutation in exon 14 of DPYD in a CRC population treated with 5-FU was 2.7%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our study, heterozygous 1003G[T (Val335Leu) was found from a patient On the other hand, Caucasians and Japanese share four variations: *5 (Ile543Val), *9 (Cys29Arg), Met166Val, and *6 (Val732Ile), although their allele frequencies were different, especially for *9 (Table 4). Because they have not necessarily correlated with phenotypic changes (e.g., differences in DPD enzyme activity, 5-FU pharmacokinetics and pharmacodynamics) (Collie-Duguid et al 2000;Johnson et al 2002;Zhu et al 2004;Seck et al 2005;Ridge et al 1998aRidge et al , 1998bHsiao et al 2004), all of these variations are generally accepted as common polymorphisms that result in unaltered function. Consistent with this, van Kuilenburg et al (2002) suggested that the Fig.…”
Section: Discussionmentioning
confidence: 99%